PENGARUH KOMITE AUDIT, KINERJA LINGKUNGAN, DAN PROFITABILITAS TERHADAP PENGUNGKAPAN EMISI KARBON: STUDI PADA PERUSAHAAN PERTAMBANGAN BEI 2019–2023 DENGAN PENDEKATAN DATA PANEL - Rian Bekti Safa'at; Regina Jansen Arsjah (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the influence of audit committees, environmental performance, and profitability on carbon emission disclosure in mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Carbon emission disclosure is an important indicator in assessing a company's transparency and accountability for the environmental impact of its operational activities. This study uses a quantitative approach with a panel data regression method. The sample was selected using a purposive sampling technique and consisted of 21 companies over five years of observation, resulting in 105 observation data. Model testing was carried out using the Chow, Hausman, and Lagrange Multiplier tests to determine the best model, and the results showed that the Random Effect Model (REM) was the most appropriate model. The results showed that environmental performance (PROPER) had a positive and significant effect on carbon emission disclosure. In contrast, profitability (ROA) and the audit committee did not show a significant effect. These findings indicate that a company's commitment to the environment is more influenced by actual environmental performance than governance or financial factors. This study provides implications for regulators and investors to pay more attention to environmental performance aspects as the main indicator in encouraging carbon information disclosure.